2021
DOI: 10.3390/plants10091767
|View full text |Cite
|
Sign up to set email alerts
|

The Micromorphology and Histochemistry of Foliar Mixed Indumentum of Leucas lavandulaefolia (Lamiaceae)

Abstract: Leucas lavandulaefolia Sm. (Lamiaceae) is an important medicinal plant with a broad spectrum of pharmacological activities. This study aimed at characterizing the morphology, distribution, and chemical composition of the secretions of trichomes at different developmental stages on the leaves of L. lavandulaefolia, using light and electron microscopy. Morphological observations revealed the presence of bicellular non-glandular, glandular peltate, and capitate trichomes on both adaxial and abaxial leaf surfaces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…3 ). These GTs in P. frutescens were structurally analogous to those present in other Lamiaceae plants, displaying a tripartite organization consisting of basal, stalk, and head cells [ 20 , 42 , 43 ]. In this study , we found P. frutescens PGTs are spheroid structures that accumulate oily substances during their maturation stages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 ). These GTs in P. frutescens were structurally analogous to those present in other Lamiaceae plants, displaying a tripartite organization consisting of basal, stalk, and head cells [ 20 , 42 , 43 ]. In this study , we found P. frutescens PGTs are spheroid structures that accumulate oily substances during their maturation stages.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the distribution of GTs on only one side of the leaf is not a universal phenomenon in plants that possess abundant glandular trichome tissue. More commonly, GTs are found on both the abaxial and adaxial surfaces of leaves [ 42 , 44 , 45 ]. Hence, when investigating species with GTs distributed on both sides of the leaf, the model proposed in this study requires spatial information of the GTs on both sides of the leaf, along with a cross-surface correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glandular trichomes are considered true "natural biofactories" [2] essential oils but are also for other secondary metabolism compounds, their secretion being polymorphic, depending on the species and their structure [26]. Although there are numerous studies on the morphology and histochemistry of glandular trichomes in species of the Lamiaceae family [27][28][29][30][31][32], the number of research works that refer to the Phlomis genus remains quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…Lamiaceae includes a considerable number of species that produce essential oils, secreted by glandular trichomes on leaves as well as some reproductive organs (Ascensão et al, 1999; Hanlidou et al, 1991). The structure and function of these trichomes, along with other leaf morphological characters can be used to differentiate closely related species in a systematic as well as biochemical context (Abu‐Asab & Cantino, 1987; Autunes & Sevinate‐Pinto, 1991; Cantino, 1990; Dunkić et al, 2017; Hu et al, 2012; Maurya et al, 2019; Moon et al, 2009; Naidoo et al, 2021; Xiang et al, 2010; Zhang et al, 2014). Leaf epidermal morphology, analyzed using light and scanning electron microscope (LM and SEM), also provides important systematic traits in Lamiaceae species in Korea (Jang & Hong, 2007; Jeon & Hong, 2006).…”
Section: Introductionmentioning
confidence: 99%